The Language Division's Efforts in Community-Based Arabic Speaking Skills Training - Wahab, Wahab; Yuliana, Yuliana; Padol, Almu; Mustar, Mustar; Lubis, Ali Musa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to describe the efforts of language managers in teaching Arabic speaking skills to female students and the factors that cause female students to have difficulty speaking Arabic. The type of research used in this study is descriptive qualitative. The research subjects were female students of the Khadijah Dormitory at the Al-Azkiya Modern Islamic Boarding School in Indragiri Hilir, Riau, Indonesia. The data collection instruments in this study used observation, interviews, and documentation. The data sources obtained in this study were the head of the Islamic Senior High School, Arabic teachers, language managers, and female students. The study's results: the process of mastering Arabic language skills for female students was carried out using the muhadatsah method. Factors that influence the difficulties of female students in speaking Arabic consist of internal and external factors. Internal factors: Students lack confidence in speaking Arabic, lack vocabulary, and are accustomed to using their respective regional languages. Efforts made by language administrators to improve the mastery of the Arabic language include various efforts such as: giving punishment to students who do not speak, providing jackets per room to supervise students, bringing dictionaries or kutaib wherever they are, playing Arabic songs or audio in the Islamic boarding school environment, holding Arabic language programs, and improving student discipline.